The Influence of Institutional Development and Community Participation on Community Empowerment of Very Underdeveloping Villages in West Bandung District - Yayat Rukayat; Benjamin Harits (Pasundan Social Science Development, 2022)
The main problem in this study is that Community Empowerment in West Bandung Regency has not been effective, which is indicated by the existence of five villages with very underdeveloped categories. The ineffectiveness of community empowerment in the five very underdeveloped villages is thought to be caused by institutional development that has not been maximized and community participation is still relatively low. The research approach according to the problems raised is a quantitative approach with survey methods. The population size in this study was 408, the sampling technique used was a two-level simple random sampling technique, with a sample size of 193. Data collection techniques were carried out by: Observation, distributing questionnaires and interviews. While the data analysis technique was carried out using Structural Equation Modeling (SEM) with the Linear Structural Relationship (LISREL) 8.80 application. The research results prove that both partially and simultaneously Institutional Development and community participation have a positive and significant effect on community empowerment in five very underdeveloped villages in West Bandung Regency.